Tranilast Directly Targets NLRP3 to Protect Melanocytes From Keratinocyte-Derived IL-1β Under Oxidative Stress - Zhuang, Tongtian; Li, Shuli; Yi, Xiuli; Guo, Sen; Wang, Yinghan; Chen, Jianru; Liu, Ling; Jian, Zhe; Gao, Tianwen; Kang, Pan; Li, Chunying (Frontiers in Cell and Developmental Biology, 2020)
The activation of NLRP3 inflammasome-IL-1β pathway in keratinocytes contributes to the melanocyte death via autoimmunity-dependent manner in vitiligo. As a safe small-compound drug employed frequently in clinic, tranilast (TR) is newly reported to block the activation of NLRP3 inflammasome in macrophage. Nevertheless, whether keratinocyte-derived IL-1β damages melanocytes in an autoimmunity-independent way and whether TR could ameliorate the melanocyte damage via inhibiting the NLRP3-IL-1β pathway in keratinocyte still are not clear. In the present study, we initially found that TR could impede the secretion of IL-1β from keratinocytes by interfering the NLRP3 oligomerization. More importantly, we illustrated that TR could decrease the melanocyte apoptosis, improve the melanogenesis, and have the capacity to optimize the melanosome translocation by abolishing the keratinocyte-derived IL-1β. Additionally, TR could mitigate the secretion of inflammatory cytokines such as IL-6, IL-8, TNF-α and IL-18 in keratinocytes under oxidative stress. In short, our data indicate that IL-1β plays detrimental roles in the melanocyte survival, melanogenesis, melanosome translocation and the secretion of inflammatory cytokines, and TR could be a promising therapeutic strategy in vitiligo by attenuating the keratinocyte-derived IL-1β under oxidative stress.